Drug induced secondary angle closure glaucoma- A case series (Panacea Journal of Medical Sciences, 2022)
Purpose: We report 3 cases with acute bilateral angle closure glaucoma following intake of oral chlorthalidone, mefenamic acid, topiramate.Materials and Methods: Case series.Results: All patients developed bilateral acute onset painful defective vision with shallow anterior chamber, raised intraocular pressure. Gonioscopy revealed bilateral occludable angle and ultrasonogram B scan showed shallow choroidal detachment, suggestive of drug induced non pupillary block secondary angle closure glaucoma. All patients were managed by discontinuation of causative drug and started on topical antiglaucoma medication and cycloplegic drug.Conclusion: We would like to bring this potentially sight threatening and reversible ophthalmic condition to general physician, which can be managed effectively by timely referral and intervention.